2022
DOI: 10.3389/fonc.2022.906498
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-based nomogram as predictive model for prognosis of hepatocellular carcinoma with portal vein tumor thrombosis receiving radiotherapy

Abstract: BackgroundThis study aims to establish and validate a predictive model based on radiomics features, clinical features, and radiation therapy (RT) dosimetric parameters for overall survival (OS) in hepatocellular carcinoma (HCC) patients treated with RT for portal vein tumor thrombosis (PVTT).MethodsWe retrospectively reviewed 131 patients. Patients were randomly divided into the training (n = 105) and validation (n = 26) cohorts. The clinical target volume was contoured on pre-RT computed tomography images and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Our study also did not combine clinical features in models. The majority of studies showed that imaging features combined with clinical features have a high value in predicting and diagnosing ( Stubblefield et al, 2020 ; Zhou et al, 2021 ; Huang et al, 2022 ). In future research, we will continue to enroll more cases and use the data augmentations method to addresses issues of small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also did not combine clinical features in models. The majority of studies showed that imaging features combined with clinical features have a high value in predicting and diagnosing ( Stubblefield et al, 2020 ; Zhou et al, 2021 ; Huang et al, 2022 ). In future research, we will continue to enroll more cases and use the data augmentations method to addresses issues of small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that the image-omics-based nomogram outperforms the clinical nomogram in predicting OS, with a C index of 0.73 (95% CI, 0.67–0.79) and an AUC of 0.71 (95% CI, 0.62–0.79) ( Table 1 ). 45 Cheng et al performed a retrospective analysis in which they extracted 396 image omics features from baseline CT scans, created and verified a CT-based image omics model, and developed a random survival forest model utilizing features with varying importance and minimal depth selection. The study aimed to predict the OS of patients with HCC and PVTT who underwent treatment with Drug-Eluting Beads Transarterial Chemoembolization (DEB-TACE).…”
Section: Progress Of Artificial Intelligence In Imaging Prediction Of...mentioning
confidence: 99%
“…Furthermore, certain studies exhibit a deficiency in external validation, thereby undermining the credibility of established models and hindering the integration of imaging omics into clinical practice. 45–48 …”
Section: Limitations Future and Expectationsmentioning
confidence: 99%